(untitled) (Dhaka University Journal of Biological Sciences, 2017)
A total of 11 fungal species were isolated from the 25 infected fruit samples of three varieties (Sabri, Champa and Sagor) of Musa sapientum. The isolated fungi were Aspergillus flavus Link, A. fumigatus Fresenius, A. niger van Tiegh., Colletotrichum musae (Berk. & Curt.) Arx, Curvularia brachyspora Boedijn., Fusarium semitectum Berk. & Rav. Fusarium sp. Link, Penicillium sp., Pestalotiopsis disseminata (Thum) Steyaert, Rhizopus sp. Ehrenb. and Trichoderma viride Pers. ex Gray. Fusarium semitectum showed the highest (28.61) per cent association frequency in Sabri variety whereas Fusarium sp. showed the lowest (3.33). Curvularia brachyspora showed the highest (21.11) per cent frequency in Champa variety whereas A. fumigatus showed the lowest (2.78). Fusarium sp. showed the highest (41.67) per cent frequency in Sagor variety whereas T. viride showed the lowest (3.34). Among the isolated fungi C. musae, C. brachyspora, F. semitectum, Fusarium sp. and P. disseminata were found to be pathogenic to three banana varieties. The presence of Pestalotiopsis disseminata (Thum) Steyaert in Sabri variety of banana is the first record in Bangladesh. Dhaka Univ. J. Biol. Sci. 26(1): 101-110, 2017 (January)